S-nitrosylation mediates synaptic plasticity in the retina - Tooker, Ryan E., author; Vigh, Jozsef, advisor; Tamkun, Michael, committee member; Hentges, Shane, committee member; Hoke, Kim, committee member (Colorado State University. Libraries, 2015)
Over the course of an entire day, our visual system must accommodate intensities of light that can change by a factor of 10¹⁰. In order to do so, the retina adapts to large, daily changes in natural light intensity by shifting its dynamic range of coding. For example, as morning light intensity increases, the retina implements multiple strategies that result in decreases in overall sensitivity in order to avoid saturation. However, adaptation to bright environments poses the inherent risk of losing visual information carried by dim/weak signals in complex natural scenes. Here we studied whether the light-evoked increase in retinal nitric oxide (NO) production is followed by NO-mediated, direct post-translational modification of proteins called S-nitrosylation and if it contributes to the modulation of the dynamic range of vision. In the central nervous system, including the retina, S-nitrosylation has not been considered to be significant under physiological conditions, and instead, has been primarily associated with neurodegenerative diseases. In this study, we provide immunohistochemical and proteomic evidence for extensive S-nitrosylation that takes place in the goldfish and mouse retinas under physiologically relevant light intensities, in an intensity-dependent manner. Functionally, we report a novel form of activity-dependent synaptic plasticity via S-nitrosylation: a “weighted potentiation” that selectively increases the output of Mb-type bipolar cells in the goldfish retina in response to weak inputs but leaves the input-output ratio for strong stimuli unaffected. Importantly, the NO action resulted in a weighted potentiation of Mb output in response to small (≤-30 mV) depolarizations. Our data strongly suggest that in the retina, light-evoked NO production leads to extensive S-nitrosylation and that this process is a significant post-translational modification affecting a wide range of proteins under physiological conditions. S-nitrosylation may function to extend the dynamic range of vision by counteracting the decreases in retinal sensitivity during light adaptation ultimately preventing the loss of visual information carried by dim scotopic signals. Finally, our results may set the framework for exploring the role of S-nitrosylation in certain neurodegenerative retinal diseases that are associated with toxic levels of NO.
Keywords: nitric oxide; S-nitrosylation; retina; bipolar cells